2016
DOI: 10.1071/fp15262
|View full text |Cite
|
Sign up to set email alerts
|

Variable P supply affects N metabolism in a legume tree, Virgilia divaricata, from nutrient-poor Mediterranean-type ecosystems

Abstract: Virgilia divaricata is an indigenous forest margin legume growing in nutrient richer soils, but it is also known to invade the N and P poorer soils of the mature fynbos.This implies that the legume has a functional tolerance for variable soil N and P levels. It is not known how the legume utilizes inorganic N from soil and atmospheric sources under variable P supply. Moreover, very little is known about how P deficiency affects root nodule metabolic functioning of V. divaricata and their associated energy cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 69 publications
2
14
0
Order By: Relevance
“…S3 and Dataset S2). Our results confirmed the role of NADH-GDH in detoxification of NH 4 + and also, the supply of glutamate for glutamine synthesis (42).…”
Section: Discussionsupporting
confidence: 78%
“…S3 and Dataset S2). Our results confirmed the role of NADH-GDH in detoxification of NH 4 + and also, the supply of glutamate for glutamine synthesis (42).…”
Section: Discussionsupporting
confidence: 78%
“…In the four species, in the water treatment, the greatest number of nodules was observed in the Inoc + low P treatment and the highest N accumulation occurred in the Inoc + high P plants (Figure 5), which coincides with a peak in plant biomass production in the four species (Figure 1). However, in the water-stressed plants, N and P accumulation did not differ between Inoc + high P and Inoc + low P and that can only be explained by a more efficient nodulation in the water-stressed plants following the same pattern as in other leguminous species [4,34,35,36,37]. This behavior has been already described in other species in the Genistea family under several stresses [38,39].…”
Section: Discussionsupporting
confidence: 67%
“…It was shown that nitrate impacts negatively on Rhizobium -infection as well as on the ratio of the nodule dry mass to the whole plant mass (Luciñski et al, 2002). As BNF is a costly process, it may be more beneficial for legumes from low nutrient ecosystems to take up N via its roots and to reduce energetically costly BNF (Magadlela et al, 2015). Similar trends were also observed in white clover where N concentration was unaffected by P deficiency.…”
Section: Discussionmentioning
confidence: 99%